Romanian Students’ Opinions on Implementing Artificial Intelligence in Higher Education: A Qualitative Approach - Pisica, Alina Iorga; Ioan, Roxana; Bucur, Louisa-Maria; Popa, Alexandru; Zaharia, Rodica Milena (Transformations In Business & Economics, 2024)
This qualitative study addresses the perceptions of Romanian Social Sciences students regarding the implementation of Artificial Intelligence (AI) in Higher Education (HE), analysing the responses of 70 participants from three Romanian universities. The results highlight both recognition of AI’s potential to transform education by improving access to information, personalizing learning, and enhancing academic performance, and concerns about technology dependence, ethical issues, data security, and impact on critical thinking and social interactions. While students appreciate the benefits of AI, such as administrative efficiency and improved learning and teaching process, they also express concerns about the loss of essential human skills and privacy and security risks. These findings underscore the importance of a balanced and ethical approach to adopting AI in educational contexts, emphasising the need for strategies that enhance technological benefits, while minimizing potential risks. The study suggests that HE institutions should concentrate on developing inclusive policies that consider the social and personal consequences of AI implementation, thus providing valuable directions for future educational research and policy.